An analysis of the doctor-patient relationship with reference to the celebrity or famous patient-issues pertaining to privacy and confidentiality - Carstens, Pieter Albert, 1960- (University of Pretoria, 2020)
Mini Dissertation (MPhil)--University of Pretoria, 2019.